2016
DOI: 10.7575/aiac.ijalel.v.6n.1p.39
|View full text |Cite
|
Sign up to set email alerts
|

The Production of Yes/No Questions, Wh-Questions, and Embedded Clauses as Functional Categories at the Initial Stage of Child L2 Acquisition

Abstract: This is a longitudinal case study of two Farsi-speaking children learning English: ‘Bernard’ and ‘Melissa’, who were 7;4 and 8;4 at the start of data collection. The research deals with the presence or absence of functional categories (CP),in our case Yes/no questions, Wh-questions, and embedded clauses as well as their production rate in early stages of interlanguage development of the child second language (L2) acquisition of syntax. Some studies in the field of child second language acquisition regarding th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…They conclude that infinitival and participial relative clauses constructions emerged at early stages in the child's English L2 acquisition. Meanwhile, a quite different result has been reported by Mobaraki & Saed (2016) who summarize that the functional category, such as questions and embedded clauses, is not present at the initial stages of L2 acquisition and emerges after the learners have mastered inflectional phrases (IP) in their grammars.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…They conclude that infinitival and participial relative clauses constructions emerged at early stages in the child's English L2 acquisition. Meanwhile, a quite different result has been reported by Mobaraki & Saed (2016) who summarize that the functional category, such as questions and embedded clauses, is not present at the initial stages of L2 acquisition and emerges after the learners have mastered inflectional phrases (IP) in their grammars.…”
Section: Discussionmentioning
confidence: 87%
“…At first, Krashen (1982 cited by Paradis, 2008) show that order sequence of morpheme acquisition is similar to that found in L1 English: for example, early-acquired morphemes in English L2 are progressive [-ing] and plural [-s]; late-acquired morphemes are past tense [-ed] and third person singular [-s] (Paradis, 2008). Moreover, clausal level of acquisition has been deeply explored by Mobaraki & Saed (2016) and Yamaguchi & Kawaguchi (2016). Mobaraki and Saed (2016) concluded that functional categories, such as Yes/No Questions, WH-questions, and embedded clauses, are not emerged in early stages of interlanguage development of the child L2 acquisition.…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations